A corrugated flexible composite skin for morphing applications. (15th December 2017) - Bai, J.B.; Chen, D.; Xiong, J.J.; Shenoi, R.A.
Abstract: This paper deals with a novel corrugated flexible composite skin (FCS) for morphing application. The FCS is constructed with two thin-walled curved fibre-reinforced-plastics (FRP) composite shells which can be extended through pure elastic deformation during a large deformation process. Thus, the area of the FCS can be changed significantly. Geometrical equations are established for describing the extensional deformation of the FCS. Based on equilibrium equations and laminate theory, analytical solutions are derived for calculating the mechanical properties of the FCS in an extensional deformation process. In order to validate the FCS design and the analytical model, FCS specimens made from T300/5228 prepreg were fabricated using vacuum bag and co-bonding methods. Tensile tests on the FCS specimens were successfully carried out. Load versus displacement curves, tensile stiffness versus tensile load curves and relative deformation versus tensile load curves were measured. Comparisons between the theoretical predictions and the experiments were conducted. It is shown that the predictions using the new model correlates well with the experiments. The theoretical analysis and experimental validation thus show that the new FCS design was effective and feasible.